Determinants of Midwife Performance: Integration of Self Efficacy, Work Engagement and Work Commitment - Kartina (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
This study aims to analyze the determinants of midwife performance in Kendari City by integrating the influence of Self Efficacy, the mediating role of Work Engagement, and the role of Work Commitment moderation. Using a quantitative approach with an explanatory design, this study involved 210 midwives in the Kendari City area as respondents. Data were collected through a structured questionnaire survey and analyzed using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The results of the study show that Self Efficacy has a fundamental role in improving midwife's performance directly, as well as being a strong predictor in building Work Engagement. Furthermore, Work Engagement has been proven to have a positive and significant effect on the performance of midwives. The crucial finding that became a novelty in this study was the role of Work Commitment as a moderation variable; The test results prove that work commitment acts as a catalyst that strengthens the positive influence of Work Engagement on midwifery performance. This means that the performance of midwifery services will reach an optimal point when midwives have high self-efficacy, feel attached to their work, and are supported by a strong commitment to the organization.